Peningkatan Pemahaman Literasi Moneter Masyarakat Desa Kutalimbaru melalui Kampanye Cinta, Bangga, Paham Rupiah - Muhammad Anwar; Ahmad Zaki Sinulingga; Muhammad Nabil Nasution; Mahesa Marpaung; Siti Aisyah (Pusat Riset dan Inovasi Nasional, 2026)
The rupiah plays a vital role as a symbol of national identity and sovereignty, but awareness among rural communities about its function and importance is often limited. In Kutalimbaru Village, the main challenges identified are low monetary literacy, which results in physical damage to money and a lack of awareness about counterfeit money. Through the Real Work Lecture (KKN) program, community service efforts were carried out with the aim of internalizing the values of “Love, Pride, Understanding (CBP) of the Rupiah.” The approach used was community-based education through interactive workshops and practical demonstrations on money care techniques and an introduction to the security features of the Rupiah. Findings in the field show a transformation in the community's attitude; from being indifferent to being more careful in handling paper money and better understanding the role of the Rupiah in economic stability. This program has succeeded in increasing the financial literacy of citizens while strengthening the spirit of nationalism through appreciation of the national currency. Keywords: community empowerment, micro businesses, tempeh products, entrepreneurship, Sialaman Village.